TEST-TAKING ANXIETY OF UNIVERSITY OF TECHNOLOGY' STUDENTS (Journal of the College of Basic Education, 2022)
It is to be noticed that increasing of testing in colleges, teachers and instructors need to recognize the role test anxiety plays in students' performance and implement effective strategies to assess students who are over shared this activity. Teachers are responsible to raise and measure students' learning ability within their classrooms; they are also responsible to prepare students for testing. In this respect, teachers must examine, develop and implement strategies to help students receive educational benefits that may increase their test scores (Mc Donald, 2001:90f). Anxiety today, is a common phenomenon of every day's life. It plays an essential role in human life because all of us are the victims of anxiety in different ways. For this, a test-taking anxiety questionnaire (Nist and Diehl, 1990:1) was used to measure the degree of test-taking anxiety of 58 B.A. of computer science students. The results show that 50% of the students are experiencing healthy test anxiety and 50% of them are experiencing unhealthy test anxiety and need some help to overcome their anxiety.